Orderly Charging Strategy and Application Effect of PV-DC Intelligent EV Chargers - Yifeng DING; Shuang ZENG; Baoqun ZHANG; Liyong WANG; Chang LIU; Zhi FU; Ji ZHANG (Zhongguo dianli)
To achieve the goal of carbon peaking and carbon neutrality , building rooftops can be an important scenario for distributed photovoltaics, and electrification of vehicles is a key measure for carbon reduction in the transportation sector. However, the large amount of photovoltaic output and electric vehicle charging demand are mismatched in time, which puts great pressure on the stability of the power grid. This paper proposes an orderly charging strategy for photovoltaic-direct current (PV-DC) intelligent charging station, which can reduce external power supply while meeting charging demand, thus effectively improving the photovoltaic self-consumption capacity and load satisfaction rate. Taking an office building in Beijing as an example, the system performance and technical advantages under different working conditions were analyzed through actual testing and simulation calculations. The results show that the proposed strategy can fully utilize the building photovoltaics to meet the electric vehicle charging demand without the need for external power supply. The load satisfaction rate can reach 100%. Compared with the traditional constant power charging method, the photovoltaic self-consumption rate increased by 42%, while the maximum photovoltaic grid-connected power decreased by 54%. The proposed strategy can provide a reference and guidance for the efficient utilization of building photovoltaics and the electrification of the transportation industry.